2018
DOI: 10.1177/1099636218761321
|View full text |Cite
|
Sign up to set email alerts
|

Axial crushing and transverse bending responses of sandwich structures with lattice core

Abstract: The performance of sandwich structure with expanded metal sheets as the core was studied under axial crushing and transverse impact bending. Relationships between the force and displacement at the mid-span of the sandwich beams were obtained from the experiments. Numerical simulations were carried out using ABAQUS/EXPLICIT and the results were thoroughly compared with the experimental results. Then, the influence of the cell orientation and size of the cell were investigated. It was shown that the cell orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A lot of variants of the lattice core geometry (pyramidal, hourglass, auxetic, Kagome structures, etc.) have been suggested for the sandwich shells, panels and beams [1][2][3][9][10][11]. Impact strength of sandwich structures with lattice cores have been intensively investigated and compared with other type of the cores (see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of variants of the lattice core geometry (pyramidal, hourglass, auxetic, Kagome structures, etc.) have been suggested for the sandwich shells, panels and beams [1][2][3][9][10][11]. Impact strength of sandwich structures with lattice cores have been intensively investigated and compared with other type of the cores (see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Taghipoor and Damghani Nouri found that an increase in the cell angle of sandwich beams with an expanded metal core, up to θ = 90 degrees, increased axial and bending energy absorption by 624.4%. Numerical situations were also carried out using ABAQUS/EXPLCIT and the results were compared to the experimental data [11]. In a separate study, the same authors found that an increase in the size of the expanded metal cell core within a reasonable range improved the performance of a structure under bending collapse [12].…”
Section: Introductionmentioning
confidence: 99%
“…Various fabrication techniques including investment casting [9], metal folding [10] and extrusion [11], interlocking assembly [12] and hot-pressing molding [13] were exploited. Meanwhile, the properties of the compression [14,15], shear [16,17], bending [18,19], impact resistance [20,21] and multifunction [22,23] are deeply investigated to comprehensively evaluate the lattice sandwich structures.…”
Section: Introductionmentioning
confidence: 99%